1989
DOI: 10.1113/jphysiol.1989.sp017500
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to brief static contractions in man with topical nervous blockade.

Abstract: SUMMARY1. We tested the hypothesis that afferent nerves from working muscles are important in determining the heart rate and blood pressure responses to brief maximal static exercise.2. In twenty human subjects, the heart rate and arterial blood pressure responses to a brief maximal voluntary handgrip were studied before and after axillary nerve anaesthesia or to maximal one-leg knee extension before and after epidural anaesthesia at L3-L4. Maximal knee extension could not be acomplished without performing a '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 10 publications
0
7
1
1
Order By: Relevance
“…This view has been supported by further human studies where anaesthesia of muscle afferents was shown to reduce the heart rate response despite the fact that the force of contraction was maintained (e.g. Lassen, Mitchell, Reeves, Rogers & Secher, 1989). In contrast, the results of other human studies have stressed the importance of central mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 43%
“…This view has been supported by further human studies where anaesthesia of muscle afferents was shown to reduce the heart rate response despite the fact that the force of contraction was maintained (e.g. Lassen, Mitchell, Reeves, Rogers & Secher, 1989). In contrast, the results of other human studies have stressed the importance of central mechanisms (e.g.…”
Section: Introductionmentioning
confidence: 43%
“…8). Although such a relationship is not as clear during high intensity isometric contractions (107,184) and maximal dynamic exercise (104). Studies employing additional strategies to modulate central command input such as electrical stimulation of resting skeletal muscle (180), hypnosis (49,339,370,379,380), muscle tendon vibration (113,155,246), and patients with unilateral limb weakness (151,385) or sensory neuropathies (61) have also demonstrated a role for central command in mediating the cardiac acceleration and increases in BP in response to exercise.…”
Section: Central Command During Steady-state Exercisementioning
confidence: 95%
“…neural inputs from higher centres of the brain, possibly the motor cortex, influencing those regions of the brain controlling the cardiovascular system, whereas the peripheral theory proposes that sensory information from receptors in exercising muscle is responsible for the cardiovascular response to exercise (Alam & Smirk, 1937). Studies in humans seem to indicate that the initial immediate increase in heart rate, due to vagal withdrawal (Freyschuss, 1970), is due entirely to afferent activity originating in the contracting muscles (Lassen, Mitchell, Reeves, Rogers & Secher, 1989).…”
Section: Discussionmentioning
confidence: 99%